Anti-glomerular basement membrane disease: an update on subgroups, pathogenesis and therapies. Issue 11 (29th October 2018) - Segelmark, Mårten; Hellmark, Thomas
Abstract: Most patients with anti-glomerular basement membrane (anti-GBM) disease present with rapidly progressive glomerulonephritis with or without pulmonary haemorrhage; however, there are several variants and vigilance is necessary to make a correct diagnosis. Such variants include overlap with anti-neutrophil cytoplasm antibodies-associated vasculitis and membranous nephropathy as well as anti-GBM occurring de novo after renal transplantation. Moreover, patients can present with isolated pulmonary haemorrhage as well as with negative tests for circulating anti-GBM. Virtually all patients with anti-GBM disease have autoantibodies that react with two discrete epitopes on the α3 chain of type IV collagen. Recent evidence suggests that healthy persons have low-affinity natural antibodies reacting with the same epitopes, but most people are protected from developing disease-causing high-affinity autoantibodies by human leukocyte antigen-dependent regulatory T-cells (Tregs). The α3 chain-derived peptides presented by the HLA-DR15 antigen lack the ability to promote the development of such Tregs. The detection of anti-GBM in circulation using the rapid assay test has led to early diagnosis and improved prognosis. However, our present tools to curb the inflammation and to eliminate the assaulting antibodies are insufficient. Only about one-third of all patients survive with functioning native kidneys. More effective therapies need to be developed; agents that inhibit neutrophil recruitment, deplete B cells and cleave immunoglobulin G (IgG) in vivo may become new weapons in the arsenal to combat anti-GBM disease.